The role of values in strategy execution in Absa Capital - Ndlovu, Hamilton (My University, 2015)
The purpose of this research was to explore the implementation or execution of strategy by the Group. The research sought to understand how well Absa Capital‟s value system was integrated into the execution of the strategy. The study also analysed whether there are common trends within the strategy implementation adopted throughout the group. Clients trust in banks, and the market and onerous regulation and legislation have changed the way in which a bank does business. These challenges and profitability pressures have necessitated banks to look at new ways of marketing, and cost saving, both of which entail strategic changes and a new approach to client engagement. Although traditional banking is understood to focus on lending and savings, the trend over the last decade has been to offer more financial solutions such as investment and insurance, through what is termed „bancassurance‟. This holistic approach looks for a bank to offer clients a one-stop financial service, whilst taking a deeper share of the client‟s wallet. A qualitative study was conducted where 33 in-depth interviews were conducted with representatives from Absa Capital. Results revealed both strong similarities and significant discrepancies in terms of the strategy execution. Shared values: while the core values of the Group permeated, the company focused on specific core values given the stages of their respective life cycles. Strategy: the company emphasises innovation, product development and product differentiation. The research has implications for start-up businesses in the financial services sector, Discovery„s international expansion plans and provides an understanding of what drives the businesses.
Keywords: ABSA Bank. Banks and banking ;Strategic planning -- South Africa